2022
DOI: 10.1128/msystems.00022-22
|View full text |Cite
|
Sign up to set email alerts
|

Performance Characteristics of Next-Generation Sequencing for the Detection of Antimicrobial Resistance Determinants in Escherichia coli Genomes and Metagenomes

Abstract: Systematically determining Illumina sequencing performance characteristics for detection of ARGs in metagenomic samples is essential to inform study design and appraisal of human, animal, and environmental metagenomic antimicrobial resistance studies. In this study, we quantified the performance characteristics of ARG detection in E. coli genomes and metagenomes and established a benchmark of ~15× coverage for ARG detection for E. coli in metagenomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 58 publications
2
7
1
Order By: Relevance
“…These bla CTX-M genes were found in contigs assembled from the metagenome data of the three samples, and the coverage of the three contigs was 777 (top 0.02 % among all contigs for coverage), 19.6 (top 3 %) and 2.0 (top 59 %) (), indicating that antimicrobial genes could be detected in contigs with a coverage of at least 2.0 and within the top 59 %. This result is consistent with that of a previous study [29] that reported median ARG detection rates ranging from approximately 60 to 90 % among E. coli ARGs under conditions of 2× genome coverage. In other words, if coverage is lower than this, such a low-abundance gene may not be detected in the metagenomic data (corresponding to the bottom right in Fig.…”
Section: Resultssupporting
confidence: 93%
“…These bla CTX-M genes were found in contigs assembled from the metagenome data of the three samples, and the coverage of the three contigs was 777 (top 0.02 % among all contigs for coverage), 19.6 (top 3 %) and 2.0 (top 59 %) (), indicating that antimicrobial genes could be detected in contigs with a coverage of at least 2.0 and within the top 59 %. This result is consistent with that of a previous study [29] that reported median ARG detection rates ranging from approximately 60 to 90 % among E. coli ARGs under conditions of 2× genome coverage. In other words, if coverage is lower than this, such a low-abundance gene may not be detected in the metagenomic data (corresponding to the bottom right in Fig.…”
Section: Resultssupporting
confidence: 93%
“…This suggests that NTS results can also rapidly provide potentially useful evidence in clinical scenarios where culturing and phenotypic resistance information cannot be obtained. However, it's worth noting that, in comparison to pathogen identi cation, the accuracy of high-throughput sequencing techniques in detecting and predicting antibiotic resistance genes is more challenging, involving several ongoing issues: (1) the comprehensiveness, of functional annotations, and the timeliness of updates of antibiotic resistance gene mutations in resistance databases [20]; (2) accurately associating genotypic resistance with phenotypic resistance in multi-microbial samples [33]; (3) establishing standardized bioinformatics analysis pipelines [34]; (4) improving sequencing depth to enhance sensitivity [35]. Currently, clinicians need to consider a patient's prior antibiotic usage history and their response to treatment to determine whether adjusting the treatment plan based on the resistance information provided by NTS tests.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, filtering out these false positives by enforcing strict settings might also result in loss of sensitivity as some true positives could be discarded ( Sun et al, 2021 ; Portik et al, 2022 ). This was experienced by Rooney et al (2022) who tested different filtering strategies on KMA output data to improve AMR gene detection, resulting in a decrease in false positives, and the detriment of true positives. To avoid this, instead of setting a minimum threshold that will eliminate part of the results, confidence detection levels were elaborated in the present study, allowing an increase in the specificity of KMA without sacrificing its sensitivity.…”
Section: Discussionmentioning
confidence: 99%